2001
DOI: 10.1177/070674370104600805
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Studies of Antisocial Behaviour

Abstract: Specu la tion about the physi cal and neu roa na tomi cal aspects of crimi nal be hav iour be gan with Franz Jo seph Gall at the end of the 18th cen tury. His ob ser va tions evolved into phre nol ogy, a the ory that as signs spe cific men tal func tions to to pog raphi cal re gions of the skull (1). Un til re cently, EEG was one of our main meth ods of look ing at brain ab nor malities in cases of ag gres sive be hav iour, but the non spe cific and rela tively un lo cal ized na ture of the find ings lim ited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 35 publications
0
16
0
5
Order By: Relevance
“…In sum, structural and functional aberrations of the frontal-limbic structures are suggested to be associated with antisocial behavior in adult samples (for more extensive reviews see Bassarath, 2001;Blair, 2003).…”
Section: Current Neuroimaging Data Of Antisocial Behavior In Adults mentioning
confidence: 99%
“…In sum, structural and functional aberrations of the frontal-limbic structures are suggested to be associated with antisocial behavior in adult samples (for more extensive reviews see Bassarath, 2001;Blair, 2003).…”
Section: Current Neuroimaging Data Of Antisocial Behavior In Adults mentioning
confidence: 99%
“…Prefrontal deficits were shown in intermittent explosive disorder (characterized by outbursts of anger; [56]) antisocial aggressive behavior [57], impulsive aggression (characterized by problems in emotion regulation; [58]) etc. In line with these human findings, the destruction of the orbital cortex increased aggressiveness in rats, whereas the stimulation of the prefrontal, piriform, and cingulated cortices reduced feline quiet biting induced by hypothalamic stimulation [43,59].…”
Section: Prefrontal Cortical Areasmentioning
confidence: 99%
“…They are both important for decoding emotional information and guiding goaldirected behaviors [3]. Many brain imaging studies have demonstrated functional and morphologic brain abnormalities in the prefrontal cortex and the amygdala in aggressive persons [4,5]. Aggressive behavior has been assumed to arise from an abnormal processing of affective information [6].…”
Section: Introductionmentioning
confidence: 99%